Otimização da produção de lacase pelo Pleurotus ostreatus na presença de lignina e análise de metabólitos por CLAE - Franco, Paula Consoli Ireno (2019)
The development of new biotechnological processes is necessary in order to add value to lignin, which is a natural and rewewable biopolymer found in the plant cell wall, and is constituted by aromatic and phenolic residues. The wood-decaying basidiomyceteous and ascomyceteous fungi are producers of ligninolytic enzymes that catalyze lignin degradation through oxidative depolymerization. The biodegradation of lignin into its constituent compounds add value to it, because different products are obtained, which are useful in different industries. In this work the fungi Botryosphaeria. ribis, Ganoderma lucidum and a strain of Pleurotus ostreatus Florida were evaluated as laccase producers, in order to select the best producer of this polyphenol oxidase, which is a ligninolytic enzyme, that collaborates in lignin biodegradation. P. ostreatus produced highest laccase titers, and was selected for enzyme optimization by a 33 factorial statistical design to evaluate the variables: lignin concentration (0 to 0.25 % w/v), yeast extract concentration (0 a 4 % w/v) and time of cultivation (4 to 10 days) on laccase production. Lignin was the main variable which increased laccase production measure against 2,6-Dimethoxyphenol (DMP) as substrate to determine enzyme activity. Optimal laccase production (5.73 U/mL) was obtained using lignin 0.87 g% w/v, yeast extract 4,5 g% w/v and 10 days of cultivation. The extracellular fluid (ECF) obtained under the optimized culture condition was treated by partition liquid-liquid with ethyl acetate in order to determine the lignin degradation products by High Performance Liquid Chromatography (HPLC). The liquid-liquid extraction procedures were validated using analytical standards. Lignin degradation products were analyzed by HPLC, and indicated unknown peaks. The analysis using UV wavelength (220, 272, and 309 nm) showed the presence of several peaks, and the samples are being dentified.